Perancangan Sistem Informasi Pelayanan Data Berbasis Web Pada Stasiun Klimatologi Kelas II Jambi - Ade Novia Maulana; Putri Yani Anjali; Nadia Syahira; Dewi Lupiani; Dhian Kurnia Ferdiansyah Irawan; Putra Dwi Pratama Lubis; Ali Imron (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
The Jambi Class II Climatological Station is the agency responsible for providing climate data and information to the public and relevant agencies. In practice, the process of handling data requests is still carried out conventionally, resulting in relatively long processing times for document management, archiving, and user service. This situation has led to several challenges, such as inefficient administrative processes, a high risk of document loss, and limitations in monitoring the status of data requests. This study aims to design a web-based Data Service Information System that can support the digitalisation of climate data services at the Class II Jambi Climatology Station. The system development method used is the prototype method, as it allows the development process to be carried out in stages based on user needs. The system design was carried out using the Unified Modelling Language (UML) as a modelling tool to describe system requirements, process flows, and user interactions with the system. The design results show that the developed system is capable of facilitating the online submission of data requests, tracking the status of requests, and managing the service database in a more structured manner. The system also provides a digital archiving feature that simplifies the management and retrieval of data request documents. The implementation of this system is expected to improve the efficiency of service processes, speed up data request processing times, enhance service transparency, and support improvements in the quality of public services at the Class IV Jambi Climatological Station.